Prevention of Postpartum Urinary Retention with Peppermint Oil Vapor - Dewi Aryanti; Yudi Triguna (JURNAL PENDIDIKAN KEPERAWATAN INDONESIA, 2022)
ABSTRACTIntroduction. Urinary retention in the postpartum period (PPUR) is one of the health problems commonly handled using catheterization and antibiotic prophylaxis. Objective. This study aimed to look at the influence of peppermint oil on PPUR prevention. Methods. This quasi-experimental study with a control group design included 60 postpartum subjects (29 in the control group and 31 in the intervention group) with vaginal delivery (ages 17-50 years). The intervention group obtained treatment by giving 2 mL of peppermint oil, while the controlled group used mineral water in the closet before subjects sat on it for 5-10 minutes and voided. The bladder condition was further checked subjectively and manually by palpation before and after the exposure to peppermint oil (distention or no distention). Result. The relationships between variables were analyzed using the Fisher Exact statistical test, obtaining no significant effect of peppermint oil administration variables on PPUR prevention (p = 0.495, CI 95%). Discussion. PPUR is related to oxidative stress, tissue inflammation, and nerve impulse blocks. Peppermint oil is estimated to be one of the modalities in preventing health problems through antioxidant, anti-inflammatory, and antispasmodic effects. Further research is needed to validate the effect of peppermint oil on PPUR prevention. In addition, support of screening information on the condition of the bladder objectively using a bladder scanner is also needed to measure the post-void residual volume (PVRV). Conclusion. This study showed that peppermint oil on PPUR prevention has no significant effect and may require further investigation. ABSTRACTPendahuluan: Retensi urin pada masa nifas (PPUR) merupakan salah satu masalah kesehatan yang sering ditangani dengan menggunakan kateterisasi dan antibiotik profilaksis. Penelitian ini bertujuan untuk melihat pengaruh minyak peppermint terhadap pencegahan PPUR. Metode: Penelitian quasi eksperimental study dengan control group ini melibatkan 60 subjek postpartum (29 pada kelompok kontrol dan 31 pada kelompok intervensi) dengan persalinan pervaginam (usia 17-50 tahun). Kelompok intervensi dilakukan dengan meneteskansebanyak 2 mL minyak peppermint pada closet (sementara kelompok kontrol menggunakan air mineral) sebelum subjek duduk di closet selama 5-10 menit dan berkemih. Kondisi kandung kemih subjektif diperiksa secara manual dengan metode palpasi sebelum dan sesudah terpapar minyak peppermint (distensi atau tidak ada distensi). Hasil. Hubungan antar variabel dianalisis menggunakan uji statistik Fisher Exact dengan hasil tidak ada pengaruh signifikan pemberian minyak peppermint terhadap pencegahan PPUR (p = 0,495, CI 95%). Diskusi. PPUR berhubungan dengan stres oksidatif, inflamasi jaringan dan blok impuls saraf. Minyak peppermint diperkirakan menjadi salah satu modalitas dalam pencegahan melalui efek antioksidan, antiinflamasi dan antispasmodik. Penelitian selanjutnya perlu dilakukan untuk memvalidasi efek minyak peppermint pada pencegahan PPUR melalui informasi kondisi kandung kemih secara objektif menggunakan bladder scanner untuk mengukur volume residu pasca berkemih (PVRV). Kesimpulan. Studi ini menunjukkan minyak peppermint pada pencegahan PPUR belum menunjukkan efek yang signifikan dan perlu penelitian lebih lanjut.